دراسة الخواص المغناطيسية للرسوبيات الاصطناعية وعلاقتها بقيم الضغط الجاذبي للمواد الرسوبية - محمد لؤي (Latakia University Journal -Basic Sciences Series, 2018)
يعد علم المغناطيسية الأرضية (Geomagnetism) أحد أهم أقسام الجيوفيزياء الذي يدرس الحقل المغناطيسي الأرضي في الأزمنة القديمة والمعاصرة. يطلق على دراسة الحقل المغناطيسي الأرضي (Geomagnetic.field) في الأزمنة القديمة اسم الباليومغناطيسية (Paleomagnetism) أو المغناطيسية القديمة، ومن الركائز الأساسية التي يعتمد عليها هذا العلم هو دراسة مغناطيسية الصخور (Rock.magnetism). وتعتمد هذه الدراسة بشكل أساسي على دراسة التمغنط الموجه للصخور الذي يتم باتجاه الحقل المغناطيسي الأرضي المطبق لحظة تشكل الصخر. يبين هذا البحث طريقة جديدة لدراسة خواص الرسوبيات المغناطيسية، باستخدام نموذج الأحواض الرسوبية الاصطناعية المخبرية، وتقريب هذه الدراسة من الظروف الطبيعية لتشكل الصخور، التي ترتبط مع رص الرسوبيات أو الضغط الجاذبي للمواد الرسوبية، وخواصها المغناطيسية مثل: الحقل المغناطيسي المطبق H، ومركبة التمغنط الموجه ، وميل مركبة التمغنط الموجه j، والأنيزوتروبية المغناطيسية، وغيرها... Geomagnetism is considered an important branch of geophysics which deals with magnetic fields over ancient and recent eras. The study of geomagnetic field in the ancient era is called paleomagnetism, however, the basic idea of this science depends on studying rock magnetism. This paper basically depends on the concept of rock orientation magnetism , applied during the period of rock formation, geomagnetic field. This research demonstrates a new method to investigate magnetic properties of deposits using a model for studying the synthetically laboratory deposition basins. Then, we approximate these investigations to the natural conditions of rock formation which relate to the deposit packing or sediment gravity pressure and their magnetic properties, e.g., the applied magnetic field H – component of orientation magnetization - decline of orientation magnetization J – magnetic anisotropy, etc.